Soil and Vegetation Study of Lahaul and Spiti Cold Desert of Western Himalayas - Singh, R. P.; Gupta, M. K. (Indian Forester, 1990)
Soil properties and vegetation studied in different localities of Labaul and Spiti valley of Western Himalayas are briefly described. The soil is silty clay loam, silty loam in texture having more alkalinity. Organic matter content varies from 0.08 to 2.98 per cent in the soil samples collected from different localities in the area under study. The nutrients e.g. Ca, K, Na and P were observed in decreasing order in all the sites. The growth of tree species, grasses and shrubs is poor because of the short growing period which is hardly five to six months or sometimes even less. Frequency, density, abundance, relative density and Importance Value Index (I.V.I.) bave been determined for each species. Hippophae rhamnoides is an important shrub used as fuelwood and as protective hedge. Important tree species of this valley bave also been described.